2001
DOI: 10.1001/archopht.119.5.677
|View full text |Cite
|
Sign up to set email alerts
|

High Injection Pressure During Intralesional Injection of Corticosteroids Into Capillary Hemangiomas

Abstract: Background: Intralesional injection of corticosteroids is an effective treatment for tumors of the head and neck. Complications are rare but include permanent loss of vision. We designed a study to investigate the mechanism for this complication. Methods: Three fellowship-trained pediatric ophthalmologists participated in the study in a nonmasked fashion. Four patients received 5 separate treatment sessions of an intralesional injection of a 50-50 mixture of triamcinolone diacetate (40 mg/mL) and betamethasone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 43 publications
2
55
0
3
Order By: Relevance
“…[221][222][223] This complication likely results from a combination of high injection pressures (causing retrograde flow of the drug from the eyelid toward the apex of the orbit) and excessive injection volume. 224 However, in several large series of intralesional corticosteroids for periorbital lesions, this complication was not reported. Avoidance of this complication is discussed further in the subsection "Eye and Orbit" under "IHs With Special Anatomic Concerns.…”
Section: Intralesional Corticosteroidsmentioning
confidence: 98%
See 3 more Smart Citations
“…[221][222][223] This complication likely results from a combination of high injection pressures (causing retrograde flow of the drug from the eyelid toward the apex of the orbit) and excessive injection volume. 224 However, in several large series of intralesional corticosteroids for periorbital lesions, this complication was not reported. Avoidance of this complication is discussed further in the subsection "Eye and Orbit" under "IHs With Special Anatomic Concerns.…”
Section: Intralesional Corticosteroidsmentioning
confidence: 98%
“…[221][222][223] However, the actual risk is thought to be quite low and is primarily related to high injection pressure. 224,246,247 This complication is discussed in greater detail in the subsection "Eye and Orbit" under "IHs With Special Anatomic Concerns. "…”
Section: Adverse Effects Of Corticosteroid Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Injections for periocular hemangiomas are usually performed by ophthalmologists, but reports of retinal artery embolization and blindness have resulted in a reduced use of this modality. [59][60][61] The largest published case series of intralesional steroids found that the majority showed a reduction greater than 50% in volume, with the best results occurring in relatively superficial hemangiomas.…”
Section: Treatmentmentioning
confidence: 99%